PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIANSEPEDA MOTOR SCOOPY PADA PT DAYA ANUGRAHMANDIRI CABANG BATURAJA - Andika, Okta; Anwar, Yuniarti; R. Wiralaga, Harby (Journal Economics Technology And Entrepreneur, 2025)
This study is entitled The Influence of Product Quality and Price on Purchase Decisions for Scoopy Motorcycles at PT. Daya AnugrahMandiri Baturaja Branch. Based on the results of the research and discussion that have been carried out, the multiple linear regression equation Y = 5.453 + 0.538X1 + 0.170X2 was obtained, and the correlation value (R) of 0.526 is in the interval 0.40-0.599, so the relationship is moderate/sufficient. While the coefficient of determination (r square) is 0.277 or 27.7%. This value shows that the contribution of the influence of the independent variables, namely product quality (X1) and price (X2) simultaneously is 27.7% to the dependent variable, namely, the purchase decision (Y) of Scoopy Motorcycles at PT. Daya AnugrahMandiri Baturaja Branch. The t-test, the level of significance (?) used is 0.05 or 5%. While the value of the degree of magnitude (df) is sought by the formula n-k-1 (0.05df:78-2-1=75=1.992) product quality (X1) is 4.310. So, the t-count value (4.310)> t-table (1.992). So it means that there is a partial influence between product quality (X1) and purchasing decisions (Y). Likewise with the price (X2) of 1.993 and t-table 1.992. So, the t count value (1.993) > t table (1.992) means that the price (X2) has a partial effect on the purchase decision (Y) of Scoopy Motorcycles at PT. Daya AnugrahMandiri Baturaja Branch.